2012
DOI: 10.1134/s102279541111010x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of quantitative traits in crosses between two Pisum sativum subspecies with particular reference to their breeding value

Abstract: The experimental study was conducted during the period of 2008-2010 at the experimental field of the Institute of Forage Crops in Pleven. The hybridization scheme included direct and back crosses cover ing four varieties of forage pea (Pisum sativum L.), namely two spring ones, Usatii 90 and Kamerton from Ukraine, and a winter one from Bulgaria, Pleven 10. There was analyzed the inheritance of quantitative traits such as plant height, height to first pod, pod number per plant, seed number per plant, seed numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 3 publications
2
9
0
Order By: Relevance
“…The measurements of morphological traits clearly indicated that hybrids generally have higher values compared to their parents (Hamouda et al, 2012). This is congruent with the suggestion that hybridization breeding improves the productivity and yield as reported by Sarawat et al (1994), and confirmed by Ceyhan et al (2008) and Kosev et al (2012). These observations are consistent with the reports by Ceyhan et al (2008) and Kosev et al (2012) who analyzed the inheritance of quantitative traits such as plant height, days to first pod, number of pods per plant, number of seeds per plant, seed weight per plant and number of fertile nodes per plant of parental components.…”
Section: Discussionsupporting
confidence: 92%
“…The measurements of morphological traits clearly indicated that hybrids generally have higher values compared to their parents (Hamouda et al, 2012). This is congruent with the suggestion that hybridization breeding improves the productivity and yield as reported by Sarawat et al (1994), and confirmed by Ceyhan et al (2008) and Kosev et al (2012). These observations are consistent with the reports by Ceyhan et al (2008) and Kosev et al (2012) who analyzed the inheritance of quantitative traits such as plant height, days to first pod, number of pods per plant, number of seeds per plant, seed weight per plant and number of fertile nodes per plant of parental components.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the values obtained for SW were lower (38.1 in 2014 and 42.2% in 2015), whereas values obtained for NS were lower in 2014 (51.7%) and higher in 2015 (89.3%). On the other hand, Kosev et al (2012) evaluated F 1 and F 2 populations generated from different crosses between three varieties, namely Usatii 90, Kamerton and Pleven 10, and obtained low narrow heritability values (between 0.01 and 44%) for PH, NP, NS, SW and SP. BLUP is a standard method for the prediction of genotypic values free of any environmental effects.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Kosev et al . (2012) evaluated F 1 and F 2 populations generated from different crosses between three varieties, namely Usatii 90, Kamerton and Pleven 10, and obtained low narrow heritability values (between 0.01 and 44%) for PH, NP, NS, SW and SP.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the common vetch accessions had greater grain numbers compared with the results for field pea in Pleven, Bulgaria, that ranged from 17.9 to 69.1 plant −1 (Kosev et al 2012). The tested common vetch accessions had a similar thousand grains mass as the local landraces of common vetch from the region of Tokat, Turkey, with an average of 59 g (Taser et al 2005).…”
Section: Number Of Pods and Grainsmentioning
confidence: 63%